Genetic Variants of the BAFF Gene and Risk of Fatigue Among Patients With Primary Sjögren’s Syndrome - Flessa, Christina-Maria; Zampeli, Evangelia; Evangelopoulos, Maria-Eleftheria; Natsis, Vasilis; Bodewes, Iris L. A.; Huijser, Erika; Versnel, Marjan A.; Moutsopoulos, Haralampos M.; Mavragani, Clio P. (Frontiers in Immunology, 2022)
Background/Purpose: Primary Sjögren’s Syndrome (SS) is characterized by B lymphocyte hyperactivity with B cell activating factor (BAFF) acting as an important regulator. Single Nucleotide Polymorphisms (SNPs) of the BAFF gene have been implicated in the pathogenesis of several autoimmune diseases characterized by heightened fatigue levels, including primary SS. We aimed to explore potential associations between BAFF SNPs and fatigue status of primary SS patients. Methods: Fatigue status was assessed in 199 consecutive primary SS patients (Greek cohort) using the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) scale. Clinical, histological, laboratory, psychometric and personality data were also collected. DNA extracted from peripheral blood of all patients underwent evaluation for the presence of five BAFF SNPs (rs9514827, rs1041569, rs9514828, rs1224141, rs12583006) by PCR. To confirm our findings, an independent replicative cohort of 62 primary SS patients (Dutch cohort) was implemented. Finally, 52 multiple sclerosis (MS) patients were served as disease controls (MS cohort). Analysis of BAFF SNPs in association with fatigue levels was performed by the online platforms SNPStats and SHEsis and the SPSS 26 and Graph Pad Prism 8.00 software. Results: TT genotype of the rs9514828 BAFF polymorphism was significantly less frequent in the fatigued primary SS patients of the Greek cohort compared to the non-fatigued (14.1% vs 33.3%). The corresponding ORs [95%CI] in the dominant and overdominant models were 0.33 [0.15-0.72], p=0.003 and 0.42 [0.23-0.78], p=0.005 respectively. The association remained significant after adjustment for the variables contributing to fatigue in the univariate analysis (OR [95% CI]: 0.3 [0.1-0.9], p=0.026). Accordingly, in the Dutch cohort, there was a trend of lower mental fatigue among patients carrying the TT rs9514828 BAFF genotype compared to their CC counterparts (4.1 ± 2.4 vs 6.0 ± 2.2 respectively, p=0.06). The rs9514828 BAFF SNP was not significantly associated with fatigue in the MS cohort. Conclusions: We report a novel association between genetic makeup and primary SS-associated fatigue with the rs9514828 TT genotype decreasing the likelihood of fatigue development among these patients. These findings need validation in multi-center studies.